Public Opinion in the Era of Post-Rationalism: The Role of Social Media - Szwed, Robert (Roczniki Nauk Społecznych, 2025)
This article diagnoses the origins and mechanisms of the emergence of post-rational attitudes in society. It points to social media as one of the most important agents of their proliferation. Confused public opinion cannot rely on social media, where messages are increasingly created and promoted to maximize their audience’s attention by evoking emotions and tailoring messages to users’ pre-identified preferences. Experts and scientists could play an essential role in resolving the veracity of findings, but they, along with other public institutions, are losing public trust. In this situation, the messages of pseudoscience promoters and post-truth spreaders have equal value in public space to the deliberations of scientists and experts. As a result, social media contribute to forming opinions based not on facts and scientific evidence but on emotions, intuition, and subjective beliefs. The spread of such views leads to the fragmentation of society, polarization, social conflicts, and, ultimately, the weakening of democracy. The solution may be to build epistemic trust at individual, social, and institutional levels.